Sistema de porosidade do solo numa topossequência Luviossolo-Solonetz no Sul de Portugal - Monteiro, Fernando (2009)
Soils with stagnic properties occurring in Alentejo commonly have low porosity. The study of a typical soil toposequence, showed that soil pore features were significantly different amongst summit and foot/toe slope pedons. In the summit pedon the Ap1 horizon was more porous than the Ap2, both exhibiting similar void distribution patterns. Conversely, the Ap1 and Ap2 horizons of the footslope pedon had a similar pore space volume, but pores with diameter larger than 500 μm were less important in the later. Pore space volume of Bt horizons was low whatever the slope position of pedons. However, they differ significantly in terms of void type and orientation patterns. No preferred orientation patterns were found in soil voids that could be related with soil compaction, being their low porosity, namely their low “conductive” porosity, not attributable to soil compaction. Those features can instead be due to the sodicity and/or the low organic C of these soils.